Pharmacokinetics, distribution, and disposition of esaxerenone, a novel, highly potent and selective non-steroidal mineralocorticoid receptor antagonist, in rats and monkeys. (2nd December 2017) - Yamada, Makiko; Takei, Makoto; Suzuki, Eiko; Takakusa, Hideo; Kotsuma, Masakatsu; Washio, Takuo; Murayama, Nobuyuki; Inoue, Shin-ichi; Izumi, Takashi
Abstract: 1. Esaxerenone (CS-3150) is a novel non-steroidal mineralocorticoid receptor antagonist. The pharmacokinetics, tissue distribution, excretion, and metabolism of esaxerenone were evaluated in rats and monkeys. 2. Following intravenous dosing of esaxerenone at 0.1–3 mg/kg, the total body clearance and the volume of distribution were 3.53–6.69 mL/min/kg and 1.47–2.49 L/kg, respectively, in rats, and 2.79–3.69 mL/min/kg and 1.34–1.54 L/kg, respectively, in monkeys. The absolute oral bioavailability was 61.0–127% in rats and 63.7–73.8% in monkeys. 3. After oral administration of [ 14 C]esaxerenone, the radioactivity was distributed widely to tissues, with the exception of a low distribution to the central nervous system. Both in rats and in monkeys, following oral administration of [ 14 C]esaxerenone the main excretion route of the radioactivity was feces. 4. Five initial metabolic pathways in rats and monkeys were proposed to be N -dealkylation, carboxylation, hydroxymethylation, O -glucuronidation, and O -sulfation. The oxidized metabolism was predominant in rats, while both oxidation and glucuronidation were predominant in monkeys.